Jahier interventista: il ruolo di Claudel e Proudhon - Marcucci, Dario (Incontri. Rivista europea di studi italiani, 2018)
Piero Jahier’s ‘interventismo’: the role of Claudel and Proudhon This essay addresses Piero Jahier’s interventionism within the broader context of Italian Modernism. Jahier’s works – from the early articles appeared on La Voce up to Con me e con gli alpini – is investigated through the lens of the religious background of the author. In doing so, the article emphasizes the role played by two French authors, Paul Claudel and Pierre-Joseph Proudhon, in affecting Jahier’s stance on WWI. It argues that Jahier draws on Claudel’s and Proudhon’s work to shape the theoretical foundation of his interventionism. In Con me e con gli alpini, the echo of voices such as Claudel’s and Proudhon’s interacts with Jahier’s religious education, and gives a significant example of the interplay between Italian and French culture at the beginning of 20th century.